Depth Determination of the 2010 El Mayor‐Cucapah Earthquake Sequence (M ≥ 4.0). Issue 7 (12th July 2019) - Yu, Chunquan; Hauksson, Egill; Zhan, Zhongwen; Cochran, Elizabeth S.; Helmberger, Donald V.
Abstract: The 2010 M W 7.2 El Mayor‐Cucapah earthquake ruptured a zone of ~120 km in length in northern Baja California. The geographic distribution of this earthquake sequence was well constrained by waveform relocation. The depth distribution, however, was poorly determined as it is near the edge of, or outside, the Southern California Seismic Network. Here we use two complementary methods to constrain the focal depths of moderate‐sized events ( M ≥ 4.0) in this sequence. We first determine the absolute earthquake depth by modeling the regional depth phases at high frequencies (~1 Hz). We mainly focus on Pn and its depth phases pPn and sPn, which arrive early at regional distance and are less contaminated by crustal multiples. To facilitate depth phase identification and to improve signal‐to‐noise ratio, we take advantage of the dense Southern California Seismic Network and use array analysis to align and stack Pn waveforms. For events without clear depth phases, we further determine their relative depths with respect to those with known depths using differential travel times of the Pn, direct P, and direct S phases recorded for event pairs. Focal depths of 93 out of 122 M ≥ 4.0 events are tightly constrained with absolute uncertainty of about 1 km. Aftershocks are clustered in the depth range of 3–10 km, suggesting a relatively shallow seismogenic zone, consistent with high surface heat flow in this region. Most aftershocks are located outside or near the lower terminus of coseismic high‐slip patches of the main shock, which may be governed by residual strains, local stress concentration, or postseismic slip. Key Points: We determine earthquake depths of the 2010 El Mayor‐Cucapah sequence by modeling Pn depth phases and using a relative location method The 2010 El Mayor‐Cucapah earthquake sequence is mainly confined in the depth range between 3 and 10 km Most aftershocks are located outside or near the lower terminus of coseismic high‐slip patches of the main shock